A blended crosslinked nanofiltration membrane, its preparation method and application
Patent Information
- Application Number
- CN202611477565.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
外加交联剂的方式引入了新的试剂,交联剂残留在膜中会影响膜的使用,且共价交联一旦形成便不可逆转,交联程度偏高时分离层变脆,受力后容易产生缺陷,交联网络的致密化还会使膜的通量下降较多
[0028]1.本申请将羧基化聚酰胺酸与端羟基超支化聚酯共混后经凝固成膜,热亚胺化与酯化在同一程序升温热处理中完成,羧基化聚酰胺酸转化为聚酰亚胺刚性骨架,端羟基超支化聚酯的端羟基与羧基化聚酰胺酸中的羧基形成酯键,残余羧基再与锌离子配位交联,分离层的分子链间形成酯键和配位键两种化学连接,与单一交联方式相比交联结构更为完整,分离层在有机溶剂中不易溶胀,截留分子量能够长期保持稳定。酯键提供稳定的共价连接,配位键具有可逆的动态特征,受到外力或溶剂作用时可部分解离并重新形成,缓解了共价交联带来的脆性,且配位交联对传质阻力的影响较小,分离层在保持截留精度的同时兼顾了通量和力学性能。
Smart Images

Figure CN122974148A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of astaxanthin concentration materials, specifically relating to a blended crosslinked nanofiltration membrane, its preparation method, and its application. Background Technology
[0002] Astaxanthin esters are products of the esterification reaction between astaxanthin and fatty acids, primarily derived from microalgae such as Haematococcus pluvialis. They possess strong antioxidant capabilities and are used as colorants and functional ingredients in aquatic feed, food, and health products. The astaxanthin ester extract obtained from microalgae contains free fatty acids and small molecule impurities in addition to astaxanthin esters. The presence of free fatty acids affects the stability and quality of the product and needs to be removed. Furthermore, the large volume of the extract and the low astaxanthin ester content necessitate concentration to increase the concentration of the active ingredient. Therefore, deacidification and concentration are crucial steps in the refining process of astaxanthin esters.
[0003] Deacidification and concentration can be achieved using nanofiltration membrane separation. Nanofiltration membranes are pressure-driven separation membranes with retention capacities between ultrafiltration and reverse osmosis membranes. They can retain organic molecules with molecular weights of several hundred Daltons while allowing smaller molecules to pass through. By selecting an appropriate molecular weight cutoff, free fatty acids can pass through the membrane while astaxanthin esters are retained. Deacidification and concentration can be completed simultaneously in a single filtration process. Compared to traditional alkali refining deacidification, membrane separation does not introduce chemical reagents, does not damage the structure and activity of astaxanthin esters, and has lower energy consumption, making it suitable for processing heat-sensitive natural products.
[0004] However, astaxanthin ester extracts typically use organic solvents as the extraction medium, and the feed solution is an organic solvent system. This places demands on the solvent resistance of nanofiltration membranes. Currently, the most widely used nanofiltration membranes are polyamide composite membranes formed by interfacial polymerization on polysulfone-based support membranes. Polysulfone materials swell or even dissolve in organic solvents, which destroys the overall structure of the composite membrane and quickly leads to the loss of its retention capacity. Therefore, it cannot be directly used for treating such feed solutions.
[0005] To address the solvent resistance issue, existing technologies utilize polymers that are inherently solvent-resistant to form membranes. Polyimide, with its rigid structure containing benzene and imide rings in its main chain, exhibits good solvent and heat resistance and has attracted considerable attention. However, the polyimide molecular chains are only physically stacked together, lacking inter-chain chemical bonds. Prolonged immersion in organic solvents still leads to swelling, causing a shift in the molecular weight cutoff and making it difficult to maintain separation accuracy. To further improve solvent resistance, existing technologies involve crosslinking polyimide membranes. Two common approaches are: one involves adding crosslinking agents such as diamines to chemically crosslink the polyimide chains; the other involves preparing carboxylated polyimides using carboxyl-containing diamine monomers, followed by treatment with a metal salt solution to form the membrane, utilizing the coordination between metal ions and carboxyl groups to achieve crosslinking.
[0006] While the aforementioned crosslinking methods alleviate swelling issues, they still have shortcomings. Adding an external crosslinking agent introduces a new reagent, and the residual crosslinking agent in the membrane can affect its usability. Furthermore, once covalent crosslinking is formed, it is irreversible. Excessive crosslinking leads to a brittle separation layer, making it prone to defects under stress. The densification of the crosslinked network also significantly reduces membrane flux. Metal ion coordination crosslinking does not introduce an organic crosslinking agent and has a smaller impact on flux. However, relying solely on coordination bonds, the crosslinking strength is limited, and the coordination structure gradually dissociates under long-term scouring by the feed solution, resulting in insufficient structural stability of the separation layer. On the other hand, the support layer of existing solvent-resistant nanofiltration membranes is mostly made of commercially available polypropylene or polyester nonwoven fabric. These nonwoven fabrics are not resistant to organic solvents and have a large material difference from the separation layer. The separation layer and the support layer are only physically anchored together, and there is a risk of interface peeling when operating in organic solvents for a long time. There is also a lack of effective means to control the cross-sectional structure of the separation layer. When the wet membrane after coating is directly immersed in the coagulation bath, the solvent and non-solvent exchange is too fast, and the cross-section is prone to forming penetrating finger-shaped macropores. The skin layer is also prone to defects, affecting the integrity of the retention.
[0007] In summary, maintaining a stable cross-linked structure in the separation layer of a nanofiltration membrane within an organic solvent feed solution, while preserving retention accuracy and balancing flux and mechanical properties, and ensuring a strong bond between the separation layer and the support layer and an intact cross-sectional structure of the separation layer, are practical requirements for nanofiltration membranes in organic solvent separation scenarios such as astaxanthin ester extract deacidification and concentration. These are also the technical problems this application aims to solve. Therefore, it is necessary to design a blended cross-linked nanofiltration membrane, its preparation method, and its applications. Summary of the Invention
[0008] To overcome the shortcomings of the prior art, a blended crosslinked nanofiltration membrane, its preparation method, and its application are provided.
[0009] To achieve the above objectives, the present invention provides the following technical solution:
[0010] A blended crosslinked nanofiltration membrane, the nanofiltration membrane comprising a support layer and a separation layer composited on the support layer;
[0011] The support layer is a polyimide nonwoven fabric; the separation layer is obtained by coagulating carboxylated polyamic acid and hydroxyl-terminated hyperbranched polyester, solidifying the mixture into a film, and then subjecting it to thermal imidization, esterification, and coordination crosslinking; the thermal imidization and esterification are carried out in the same programmed temperature heat treatment; the esterification involves the formation of ester bonds between the terminal hydroxyl groups of the hydroxyl-terminated hyperbranched polyester and the carboxyl groups in the carboxylated polyamic acid; the coordination crosslinking involves the coordination of zinc ions with the residual carboxyl groups in the separation layer.
[0012] The carboxylated polyamic acid is obtained by copolymerization of benzophenone tetracarboxylic dianhydride, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the terminal hydroxyl hyperbranched polyester is obtained by polycondensation of pentaerythritol and dimethylolpropionic acid catalyzed by p-toluenesulfonic acid; the molecular weight cutoff of the separation layer is 500-700 Da.
[0013] The preparation method of the terminal hydroxyl hyperbranched polyester is as follows: pentaerythritol and dimethylolpropionic acid are mixed, p-toluenesulfonic acid is added, and polycondensation is carried out at 140-150℃ and vacuum degree 0.08-0.095 MPa for 3-6 h. After cooling to room temperature, the product is not purified to obtain the terminal hydroxyl hyperbranched polyester.
[0014] The molar ratio of pentaerythritol to dimethylolpropionic acid is 1:(12-28), and the amount of p-toluenesulfonic acid used is 0.5-1% of the total mass of pentaerythritol and dimethylolpropionic acid.
[0015] The method for preparing the carboxylated polyamic acid is as follows: under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid are dissolved in N-methylpyrrolidone, stirred and dissolved, and then benzophenone tetracarboxylic dianhydride is added in 3-5 portions. The mixture is polycondensed at 0-5°C for 6-10 h to obtain a carboxylated polyamic acid solution with a solid content of 16-20%.
[0016] The molar amount of the benzophenone tetracarboxylic dianhydride is equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 7:(2-4).
[0017] The carboxylated polyamic acid solution is electrospun at a voltage of 15-25 kV, a receiving distance of 15-20 cm, and a feed speed of 0.5-2 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric is fixed on a stainless steel frame and subjected to pre-imidization heat treatment. The carboxylated polyamic acid is thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0018] The steps and parameters of the pre-iminoization heat treatment are as follows: the carboxylated polyamic acid nonwoven fabric is kept at 80℃ for 0.5-1 h, at 150℃ for 0.5-1 h, and then at 250-300℃ for 1-2 h.
[0019] A method for preparing a blended crosslinked nanofiltration membrane, the method comprising the following steps:
[0020] (1) Dissolve the hydroxyl-terminated hyperbranched polyester in N-methylpyrrolidone to prepare a hydroxyl-terminated hyperbranched polyester solution with a mass fraction of 10-20%, mix it with the carboxylated polyamic acid solution, stir for 2-4 h, and let it stand to degas for 4-8 h to obtain a blended casting solution; coat the blended casting solution onto the polyimide nonwoven fabric to form a blended casting solution wet film with a thickness of 200-300 μm;
[0021] (2) The polyimide nonwoven fabric coated with the co-casting solution in step (1) is immersed in water at 15-20℃ for 5-30 s to pre-gel, and then transferred to a mixed coagulation bath with a mass ratio of water to N-methylpyrrolidone of 7:(2-4) for 3-8 min to solidify into a film. After taking it out, it is immersed in pure water for 2-4 h to wash and obtain a solidified film.
[0022] (3) Drain the solidified film and perform heat curing treatment. The carboxylated polyamic acid is heat imidized to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester are esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a heat-cured film.
[0023] (4) Immerse the thermosetting membrane in a 0.5-2% zinc acetate aqueous solution for 1-4 h. The zinc ions coordinate and crosslink with the residual carboxyl groups in the separation layer. After removal, rinse with ethanol 2-3 times and dry at 40-60℃ for 1-2 h to obtain a blended crosslinked nanofiltration membrane.
[0024] The hydroxyl-terminated hyperbranched polyester solution and the carboxylated polyamic acid solution are mixed at a dry weight ratio of (0.08-0.2):1.
[0025] The steps and parameters of the thermosetting treatment are as follows: keep at 80℃ for 1 hour, keep at 150℃ for 1 hour, and then keep at 220-250℃ for 1-2 hours.
[0026] An application of a blended crosslinked nanofiltration membrane for deacidification and concentration of astaxanthin ester extract.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0028] 1. This application involves blending carboxylated polyamic acid with hydroxyl-terminated hyperbranched polyester and then solidifying it into a film. Thermal imidization and esterification are completed in the same programmed temperature heat treatment. The carboxylated polyamic acid is transformed into a rigid polyimide backbone. The terminal hydroxyl groups of the hydroxyl-terminated hyperbranched polyester form ester bonds with the carboxyl groups in the carboxylated polyamic acid. The remaining carboxyl groups then coordinate with zinc ions for crosslinking. The molecular chains of the separation layer form both ester and coordination bonds, resulting in a more complete crosslinking structure compared to a single crosslinking method. The separation layer is less prone to swelling in organic solvents, and the retained molecular weight remains stable over a long period. Ester bonds provide stable covalent connections, while coordination bonds have reversible dynamic characteristics, partially dissociating and reforming under external forces or solvent action, mitigating the brittleness caused by covalent crosslinking. Furthermore, coordination crosslinking has a smaller impact on mass transfer resistance. The separation layer maintains retention accuracy while also considering flux and mechanical properties.
[0029] 2. This application utilizes the esterification reaction between hydroxyl-terminated hyperbranched polyester and carboxylated polyamic acid to achieve covalent crosslinking, eliminating the need for external crosslinking agents and avoiding the impact of residual crosslinking agents on membrane performance. The hydroxyl-terminated hyperbranched polyester exhibits a nearly spherical branched structure, with multiple terminal hydroxyl groups per molecule, allowing simultaneous reaction with carboxyl groups on multiple molecular chains. This ensures efficient utilization of crosslinking points. Its aliphatic segments are relatively flexible, and their embedding into the rigid polyimide network adjusts the free volume of the separation layer, preventing low flux due to overly dense packing. After polycondensation, the hydroxyl-terminated hyperbranched polyester is used directly for blending without purification, eliminating the purification process and avoiding the loss of low molecular weight fractions and terminal hydroxyl groups during purification, thus ensuring the crosslinking density during subsequent esterification.
[0030] 3. This application uses a polyimide nonwoven fabric obtained by electrospinning from the same carboxylated polyamic acid solution and pre-imidizing as the support layer. The fiber diameter is relatively fine, the nonwoven fabric has high porosity and interconnected channels, resulting in low resistance to permeation liquid, and the support layer itself is resistant to organic solvents. The support layer and the separation layer are made of the same material, and esterification and coordination reactions occur at the interface during thermosetting and coordination treatment. The separation layer and the support layer are bonded by chemical bonds, and the bonding strength is higher than that of physical anchoring. It is not easy for interfacial delamination to occur during long-term operation in organic solvents.
[0031] 4. This application employs a two-stage coagulation method: pre-gelling in water followed by transfer to a coagulation bath containing a mixture of water and N-methylpyrrolidone. The surface layer rapidly solidifies to form a complete primary skin layer, which then undergoes gentle phase separation in an environment with reduced coagulation activity. This results in interconnected, sponge-like pores in the cross-section, reducing finger-like macropores and skin defects. The separation layer structure is intact with low permeation resistance. When this blended cross-linked nanofiltration membrane is used for the deacidification and concentration of astaxanthin ester extract, small molecule impurities such as free fatty acids permeate through the separation layer, while astaxanthin esters are retained and concentrated. Deacidification and concentration are completed in a single filtration step, and the cross-linked structure ensures stable separation performance of the separation layer during long-term operation in the feed solution. Attached Figure Description
[0032] Figure 1 This is a process flow diagram of a method for preparing a blended crosslinked nanofiltration membrane according to the present invention. Detailed Implementation
[0033] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0034] The technical solution of this application is as follows:
[0035] A blended crosslinked nanofiltration membrane, the nanofiltration membrane comprising a support layer and a separation layer composited on the support layer;
[0036] The support layer is a polyimide nonwoven fabric; the separation layer is obtained by coagulating carboxylated polyamic acid and hydroxyl-terminated hyperbranched polyester, solidifying the mixture into a film, and then subjecting it to thermal imidization, esterification, and coordination crosslinking; the thermal imidization and esterification are carried out in the same programmed temperature heat treatment; the esterification involves the formation of ester bonds between the terminal hydroxyl groups of the hydroxyl-terminated hyperbranched polyester and the carboxyl groups in the carboxylated polyamic acid; the coordination crosslinking involves the coordination of zinc ions with the residual carboxyl groups in the separation layer.
[0037] The carboxylated polyamic acid is obtained by copolymerization of benzophenone tetracarboxylic dianhydride, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the terminal hydroxyl hyperbranched polyester is obtained by polycondensation of pentaerythritol and dimethylolpropionic acid catalyzed by p-toluenesulfonic acid; the molecular weight cutoff of the separation layer is 500-700 Da.
[0038] The preparation method of the terminal hydroxyl hyperbranched polyester is as follows: pentaerythritol and dimethylolpropionic acid are mixed, p-toluenesulfonic acid is added, and polycondensation is carried out at 140-150℃ and vacuum degree 0.08-0.095 MPa for 3-6 h. After cooling to room temperature, the product is not purified to obtain the terminal hydroxyl hyperbranched polyester.
[0039] The molar ratio of pentaerythritol to dimethylolpropionic acid is 1:(12-28), and the amount of p-toluenesulfonic acid used is 0.5-1% of the total mass of pentaerythritol and dimethylolpropionic acid.
[0040] The method for preparing the carboxylated polyamic acid is as follows: under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid are dissolved in N-methylpyrrolidone, stirred and dissolved, and then benzophenone tetracarboxylic dianhydride is added in 3-5 portions. The mixture is polycondensed at 0-5°C for 6-10 h to obtain a carboxylated polyamic acid solution with a solid content of 16-20%.
[0041] The molar amount of the benzophenone tetracarboxylic dianhydride is equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 7:(2-4).
[0042] The carboxylated polyamic acid solution is electrospun at a voltage of 15-25 kV, a receiving distance of 15-20 cm, and a feed speed of 0.5-2 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric is fixed on a stainless steel frame and subjected to pre-imidization heat treatment. The carboxylated polyamic acid is thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0043] The steps and parameters of the pre-iminoization heat treatment are as follows: the carboxylated polyamic acid nonwoven fabric is kept at 80℃ for 0.5-1 h, at 150℃ for 0.5-1 h, and then at 250-300℃ for 1-2 h.
[0044] A method for preparing a blended crosslinked nanofiltration membrane, such as... Figure 1 As shown, the method includes the following steps:
[0045] (1) Dissolve the hydroxyl-terminated hyperbranched polyester in N-methylpyrrolidone to prepare a hydroxyl-terminated hyperbranched polyester solution with a mass fraction of 10-20%, mix it with the carboxylated polyamic acid solution, stir for 2-4 h, and let it stand to degas for 4-8 h to obtain a blended casting solution; coat the blended casting solution onto the polyimide nonwoven fabric to form a blended casting solution wet film with a thickness of 200-300 μm;
[0046] (2) The polyimide nonwoven fabric coated with the co-casting solution in step (1) is immersed in water at 15-20℃ for 5-30 s to pre-gel, and then transferred to a mixed coagulation bath with a mass ratio of water to N-methylpyrrolidone of 7:(2-4) for 3-8 min to solidify into a film. After taking it out, it is immersed in pure water for 2-4 h to wash and obtain a solidified film.
[0047] (3) Drain the solidified film and perform heat curing treatment. The carboxylated polyamic acid is heat imidized to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester are esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a heat-cured film.
[0048] (4) Immerse the thermosetting membrane in a 0.5-2% zinc acetate aqueous solution for 1-4 h. The zinc ions coordinate and crosslink with the residual carboxyl groups in the separation layer. After removal, rinse with ethanol 2-3 times and dry at 40-60℃ for 1-2 h to obtain a blended crosslinked nanofiltration membrane.
[0049] The hydroxyl-terminated hyperbranched polyester solution and the carboxylated polyamic acid solution are mixed at a dry weight ratio of (0.08-0.2):1.
[0050] The steps and parameters of the thermosetting treatment are as follows: keep at 80℃ for 1 hour, keep at 150℃ for 1 hour, and then keep at 220-250℃ for 1-2 hours.
[0051] An application of a blended crosslinked nanofiltration membrane for deacidification and concentration of astaxanthin ester extract.
[0052] In the deacidification and concentration of astaxanthin ester extract, the feed solution is usually an organic solvent system. Conventional nanofiltration membranes mostly use polysulfone materials as the support layer and polyamide as the separation layer. Polysulfone materials will swell or even dissolve in organic solvents, causing the composite membrane structure to fail and making it impossible to directly process such feed solutions.
[0053] To address this issue, this application uses carboxylated polyamic acid as the main polymer of the release layer. After thermal imidization, the carboxylated polyamic acid is converted into polyimide. Benzophenone tetracarboxylic dianhydride residues form rigid units in the main chain, with benzene rings linked to imide rings. This restricts internal rotation of the molecular chain segments, resulting in tight interchain packing and making it difficult for solvent molecules to penetrate between the chains. Consequently, the release layer acquires solvent resistance and heat resistance. The two amino groups of 3,5-diaminobenzoic acid are located at the meta positions of the carboxyl group. During copolymerization, the amino groups participate in the chain-forming reaction, while the carboxyl groups, as side groups, hang on the main chain, not participating in chain formation and remaining intact, becoming reaction sites for subsequent crosslinking. In other words, this comonomer composition allows the release layer to obtain a rigid, solvent-resistant framework while uniformly distributing usable carboxyl groups along the framework. This is the structural basis for the subsequent two crosslinking reactions.
[0054] Carboxylated polyamic acid is prepared by low-temperature solution polycondensation. The lone pair electrons on the nitrogen atom of the amino group attack the carbonyl carbon of the anhydride group to form an amic acid structure. This reaction is exothermic and reversible, and the anhydride group is easily hydrolyzed and deactivated. Therefore, benzophenone tetracarboxylic dianhydride is added to the reaction system in stages to avoid end-group imbalance caused by local anhydride excess and side reactions caused by excessive local temperature rise, thus ensuring a steady increase in molecular weight. The low-temperature environment suppresses the reverse reaction and hydrolysis side reactions, and nitrogen protection isolates moisture and oxygen. The molar amount of benzophenone tetracarboxylic dianhydride is equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid. The equimolar reaction of the two functional groups is beneficial for obtaining carboxylated polyamic acid with a higher molecular weight, which ensures the mechanical properties of the film after formation. The ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid determines the density of side carboxyl groups on the molecular chain. If the ratio is too high, there will be insufficient carboxyl sites, resulting in limited subsequent crosslinking. If the ratio is too low, the ether bond content will decrease, the chain flexibility will decrease, and the film-forming properties will deteriorate.
[0055] A rigid framework can only delay swelling; chemical bonds are still required between molecular chains. Adding an external crosslinking agent for chemical crosslinking introduces new reagents, and the residue of the crosslinking agent affects the membrane's usability. Therefore, this application blends hydroxyl-terminated hyperbranched polyester with carboxylated polyamic acid, achieving crosslinking through the reaction of the polyester's terminal hydroxyl groups with the carboxyl groups, eliminating the need for an external crosslinking agent. The hydroxyl-terminated hyperbranched polyester is obtained through polycondensation catalyzed by p-toluenesulfonic acid, using pentaerythritol as the core and dimethylolpropionic acid as the branching monomer. Dimethylolpropionic acid contains one carboxyl group and two hydroxyl groups. The esterification reaction grows outward from pentaerythritol in a generational branching pattern, forming a nearly spherical branched structure with a large number of hydroxyl groups at the molecular ends. One molecule can simultaneously provide multiple crosslinking points. Compared to linear polymers, this branched structure exhibits less intramolecular entanglement, higher terminal functional group density, and higher reactivity. Polycondensation is carried out under vacuum, and the generated water is promptly removed, shifting the esterification equilibrium towards the formation of polyester. Polycondensation products can be directly used for blending without purification. Purification processes typically involve dissolution, precipitation, or dialysis, and low molecular weight fractions and fractions enriched with terminal hydroxyl groups are easily lost during purification. Blending without purification eliminates the purification step while preserving the terminal hydroxyl groups, ensuring their content and thus guaranteeing the crosslinking density during subsequent esterification. During blending, hydrogen bonds and polar interactions exist between the ester and hydroxyl groups of the terminal hydroxyl hyperbranched polyester and the amide and carboxyl groups of the carboxylated polyamic acid. Both achieve molecular-level dispersion in N-methylpyrrolidone, preventing macroscopic phase separation in the casting solution. This is a prerequisite for uniform distribution of crosslinking points after solidification.
[0056] During the thermosetting process, the low-temperature section with programmed temperature rise removes moisture and residual solvent from the film. As the temperature continues to rise, the carboxyl groups in the amic acid units of the carboxylated polyamic acid undergo dehydration and cyclization with adjacent amide groups to form stable five-membered imide rings, completing thermal imidization. Simultaneously, the terminal hydroxyl groups of the hyperbranched polyester and the carboxyl groups in the carboxylated polyamic acid undergo direct dehydration condensation at high temperature to form ester bonds, completing esterification. The p-toluenesulfonic acid remaining in the hyperbranched polyester is readily soluble in water and is largely removed during pre-gelation, mixed coagulation bath impregnation, and immersion washing with the aqueous phase. The esterification reaction does not depend on an external catalyst; its driving force lies in the enhanced molecular chain segment mobility in the high-temperature section, allowing the hyperbranched polyester segments to diffuse and migrate, and the terminal hydroxyl groups to fully contact the carboxyl groups and undergo thermal esterification. Thermal imidization and esterification are completed in the same programmed temperature heat treatment, with skeleton shaping and crosslinking reactions occurring simultaneously. Crosslinking points are established before the molecular chains are fully shaped, resulting in a uniformly distributed crosslinking network. If the two reactions are carried out separately, the polyimide chain that undergoes imidization first will have decreased mobility, an increased tendency for phase separation between the hydroxyl-terminated hyperbranched polyester and the polyimide, and poorer crosslinking uniformity. Ester bonds covalently link the hydroxyl-terminated hyperbranched polyester and polyimide chains. Multiple hydroxyl groups in a single polyester molecule react with carboxyl groups on different molecular chains, effectively bridging multiple molecular chains with multifunctional crosslinking points to form a three-dimensional covalent crosslinking network. The inter-chain bonding changes from physical stacking to chemical bonding, and the separation layer no longer swells in organic solvents. The aliphatic segments of the hydroxyl-terminated hyperbranched polyester are relatively flexible, with numerous cavities within the spherical molecules. Embedding them into the rigid polyimide network adjusts the free volume of the separation layer, preventing the pure polyimide separation layer from having low throughput due to excessive compaction. The separation layer maintains high throughput while preserving retention accuracy.
[0057] Ester crosslinking is an irreversible covalent crosslinking process. Excessive crosslinking can lead to brittleness in the release layer, making it prone to defects under stress. Furthermore, the amount of terminally hydroxyl hyperbranched polyester used limits esterification to only consume a portion of the carboxyl groups in the release layer, leaving residual carboxyl groups unused. Therefore, this application immerses the thermosetting film in an aqueous zinc acetate solution, allowing zinc ions to coordinate crosslink with the residual carboxyl groups in the release layer. Zinc ions possess empty orbitals that can accept lone pairs of electrons. Oxygen atoms in the carboxyl groups provide lone pairs of electrons to these empty orbitals, forming coordinate bonds. A single zinc ion can bridge multiple carboxyl groups, creating new crosslinking points between molecular chains. Unlike covalent ester bonds, coordinate bonds have moderate bond energies and are reversible dynamic interactions. When the release layer is subjected to external forces or solvents, the coordinate bonds can partially dissociate and reform, dissipating stress through this dissociation and reformation. This process maintains dimensional stability while mitigating the brittleness caused by covalent crosslinking. Since coordinate crosslinking occurs at residual carboxyl group sites, it has a smaller impact on the mass transfer resistance of the release layer, thus maintaining flux. Ester bonds provide a stable covalent backbone, while coordination bonds provide dynamically adjustable supplementary crosslinking. These two crosslinking mechanisms work together to ensure the separation layer does not easily swell during long-term operation in organic solvents, maintaining a stable molecular weight cutoff. Furthermore, zinc is a common trace element, contributing to good safety during long-term contact between the membrane and the feed solution.
[0058] Zinc acetate aqueous solution was chosen for coordination treatment because zinc acetate has good water solubility, and the carboxyl groups in the aqueous phase ionize into carboxylate ions. The coordination of carboxylate ions with zinc ions is more favorable than that with carboxyl groups. At this point, the membrane has completed thermosetting, and both the polyimide backbone and ester bond network are water-resistant; immersion in the aqueous phase will not damage the membrane structure. After treatment, the membrane is rinsed with ethanol. Ethanol is miscible with water and has low surface tension, which can displace the water inside the membrane, preventing the surface tension of water from causing the pore structure of the separation layer to collapse during drying. Low-temperature drying after rinsing yields the blended crosslinked nanofiltration membrane.
[0059] The separation layer requires a support layer to function. Commercially available polypropylene or polyester nonwoven fabrics are not resistant to organic solvents and differ significantly from the separation layer material. Their bond relies solely on physical anchoring, which carries the risk of interfacial delamination with long-term use. This application utilizes the same carboxylated polyamic acid solution for electrospinning, followed by pre-imidization heat treatment to obtain polyimide nonwoven fabric as the support layer. During electrospinning, the carboxylated polyamic acid solution forms a jet under a high-voltage electric field. As the solvent evaporates, the jet is stretched and refined, resulting in finer fibers. The resulting nonwoven fabric, formed by fiber overlap, has high porosity and interconnected channels, minimizing resistance to permeation. Pre-imidization dehydrates and cyclizes the carboxylated polyamic acid in the fibers, converting it into polyimide, thus giving the support layer inherent solvent resistance. More importantly, the support layer and the release layer are made of the same material. During the coating process, the N-methylpyrrolidone in the co-casting solution causes slight swelling of the nonwoven fabric surface, and the molecular chains at the interface interpenetrate. During heat curing, the carboxyl groups in the support layer esterify with the terminal hydroxyl groups of the hyperbranched polyester in the release layer. During coordination treatment, the carboxyl groups at the interface also coordinate with zinc ions. The release layer and the support layer are bonded by chemical bonds, and the bonding strength is much higher than that of physical anchoring. This makes them difficult to peel off during long-term operation in organic solvents. The pre-imidization temperature of the support layer is higher than the heat curing temperature of the release layer. When the release layer is heat-cured, the support layer has already completed its structural transformation and its dimensions remain stable, preventing shrinkage and deformation due to secondary heating.
[0060] The cross-sectional structure of the separation layer is controlled by the coagulation process. If the wet film after coating is directly immersed in a strong coagulation bath, the exchange between solvent and non-solvent is too rapid, easily forming penetrating finger-like macropores on the cross-section, and defects are also easily generated in the skin layer. In this application, the wet film is first immersed in water for pre-gelation, and the solvent and non-solvent on the surface exchange rapidly, resulting in instantaneous phase separation to form a complete initial skin layer. Then, it is transferred to a mixed coagulation bath of water and N-methylpyrrolidone for further coagulation. The N-methylpyrrolidone contained in the mixed coagulation bath reduces the coagulation activity of the non-solvent, the exchange between solvent and non-solvent tends to be moderate, the phase separation occurs in a delayed manner, and the cross-section develops into interconnected sponge-like pores, thus achieving both the integrity of the skin layer and the low permeability resistance of the cross-section. After coagulation, it is washed with pure water to remove residual N-methylpyrrolidone and trace amounts of p-toluenesulfonic acid in the membrane, avoiding adverse effects from residues during heat curing or membrane use.
[0061] The co-crosslinked nanofiltration membrane of this application is used for deacidification and concentration of astaxanthin ester extract, with separation based on molecular size sieving. The free fatty acids in the astaxanthin ester extract have relatively small molecular weights, while the astaxanthin ester itself has a relatively large molecular weight. The molecular weight cutoff of the separation layer lies between these two. Under pressure, free fatty acids and small molecule impurities permeate through the separation layer, while the astaxanthin ester is retained and concentrated. Deacidification and concentration are completed in the same process. The crosslinked network formed by ester and coordination bonds ensures the structural stability of the separation layer during long-term operation in organic solvent solutions, preventing molecular weight drift and maintaining separation accuracy over a long period.
[0062] This application involves blending carboxylated polyamic acid with hydroxyl-terminated hyperbranched polyester, completing thermal imidization and esterification in the same programmed temperature rise heat treatment, and then using zinc ions to coordinate crosslink with residual carboxyl groups, combined with a homologous polyimide nonwoven fabric support layer. This allows the blended crosslinked nanofiltration membrane to maintain stable retention accuracy during long-term operation in organic solvent solutions such as astaxanthin ester extract, while also taking into account flux, mechanical properties, and interlayer bonding strength.
[0063] The present invention will be described in detail below through examples and comparative examples, but the scope of protection of the present invention is not limited to these examples. Unless otherwise specified, the chemical reagents and raw materials used in the following examples and comparative examples are all conventional commercially available products. The pre-imidization heat treatment and thermosetting treatment were both carried out under nitrogen protection.
[0064] Example 1
[0065] Pentaerythritol and dimethylolpropionic acid were mixed at a molar ratio of 1:28, and p-toluenesulfonic acid was added. The amount of p-toluenesulfonic acid was 0.75% of the total mass of pentaerythritol and dimethylolpropionic acid. Polycondensation was carried out at 150°C and a vacuum of 0.0875 MPa for 3 h. After cooling to room temperature, the product was not purified to obtain a hydroxyl-terminated hyperbranched polyester.
[0066] Under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid were dissolved in N-methylpyrrolidone at a molar ratio of 7:4. After stirring and dissolving, benzophenone tetracarboxylic dianhydride was added in three portions. The molar amount of benzophenone tetracarboxylic dianhydride was equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid. Polycondensation was carried out at 5°C for 8 h to obtain a carboxylated polyamic acid solution with a solid content of 16%.
[0067] The carboxylated polyamic acid solution was electrospun at a voltage of 20 kV, a receiving distance of 15 cm, and a feed speed of 2 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric was fixed on a stainless steel frame and subjected to pre-imidization heat treatment, which involved holding at 80℃ for 0.75 h, at 150℃ for 0.5 h, and then at 300℃ for 1.5 h. The carboxylated polyamic acid was thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0068] Hydroxyl-terminated hyperbranched polyester was dissolved in N-methylpyrrolidone to prepare a 20% (w / w) hydroxyl-terminated hyperbranched polyester solution. This solution was then mixed with the carboxylated polyamic acid solution at a dry weight ratio of 0.14:1. The mixture was stirred for 4 h and allowed to stand for 6 h to remove bubbles, resulting in a co-casting solution. The co-casting solution was then coated onto a polyimide nonwoven fabric to form a 200 μm thick wet film. The polyimide nonwoven fabric coated with the co-casting solution was immersed in water at 20°C for 17.5 s to pre-gel, and then transferred to a coagulation bath containing water and N-methylpyrrolidone at a weight ratio of 7:2 for 8 min to solidify into a film. After removal, the film was immersed in pure water for 3 h to wash, resulting in a solidified film.
[0069] The coagulated membrane was drained and subjected to thermosetting treatment. It was kept at 80℃ for 1 h, 150℃ for 1 h, and then at 220℃ for 2 h. The carboxylated polyamic acid was thermoiminated to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester were esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a thermosetting membrane. The thermosetting membrane was immersed in a 0.5% zinc acetate aqueous solution for 4 h. The zinc ions were coordinated and crosslinked with the residual carboxyl groups in the separation layer. After removal, it was rinsed with ethanol 3 times and dried at 40℃ for 2 h to obtain a blended crosslinked nanofiltration membrane.
[0070] Example 2
[0071] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0072] Pentaerythritol and dimethylolpropionic acid were mixed at a molar ratio of 1:12, and p-toluenesulfonic acid was added at 1% of the total mass of pentaerythritol and dimethylolpropionic acid. Polycondensation was carried out at 140°C and 0.095 MPa for 4.5 h. After cooling to room temperature, the product was not purified to obtain a hydroxyl-terminated hyperbranched polyester.
[0073] Under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid were dissolved in N-methylpyrrolidone at a molar ratio of 7:2. After stirring and dissolving, benzophenone tetracarboxylic dianhydride was added in four portions. The molar amount of benzophenone tetracarboxylic dianhydride was equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid. Polycondensation was carried out at 0°C for 10 h to obtain a carboxylated polyamic acid solution with a solid content of 18%.
[0074] The carboxylated polyamic acid solution was electrospun at a voltage of 25 kV, a receiving distance of 17.5 cm, and a feed speed of 0.5 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric was fixed on a stainless steel frame and subjected to pre-imidization heat treatment, which involved holding at 80℃ for 1 h, at 150℃ for 0.75 h, and then at 250℃ for 2 h. The carboxylated polyamic acid was thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0075] Hydroxyl-terminated hyperbranched polyester was dissolved in N-methylpyrrolidone to prepare a 15% (w / w) hydroxyl-terminated hyperbranched polyester solution. This solution was then mixed with the carboxylated polyamic acid solution at a dry weight ratio of 0.2:1. The mixture was stirred for 2 h and allowed to stand for degassing for 8 h to obtain a co-casting solution. The co-casting solution was then coated onto a polyimide nonwoven fabric to form a 250 μm thick wet film. The polyimide nonwoven fabric coated with the co-casting solution was immersed in water at 15°C for pre-gelling for 30 s, and then transferred to a coagulation bath containing water and N-methylpyrrolidone at a weight ratio of 7:3 for 3 min to solidify into a film. After removal, the film was immersed in pure water for washing for 4 h to obtain a solidified film.
[0076] The coagulated membrane was drained and subjected to thermosetting treatment. It was kept at 80℃ for 1 h, 150℃ for 1 h, and then at 235℃ for 1 h. The carboxylated polyamic acid was thermoiminated to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester were esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a thermosetting membrane. The thermosetting membrane was immersed in a 1.25% zinc acetate aqueous solution for 1 h. The zinc ions coordinated and crosslinked with the residual carboxyl groups in the separation layer. After removal, it was rinsed with ethanol 3 times and dried at 50℃ for 1 h to obtain a blended crosslinked nanofiltration membrane.
[0077] Example 3
[0078] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0079] Pentaerythritol and dimethylolpropionic acid were mixed at a molar ratio of 1:20, and p-toluenesulfonic acid was added at an amount of 0.5% of the total mass of pentaerythritol and dimethylolpropionic acid. Polycondensation was carried out at 145°C and a vacuum of 0.08 MPa for 6 h. After cooling to room temperature, the product was not purified to obtain a hydroxyl-terminated hyperbranched polyester.
[0080] Under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid were dissolved in N-methylpyrrolidone at a molar ratio of 7:3. After stirring and dissolving, benzophenone tetracarboxylic dianhydride was added in 5 portions. The molar amount of benzophenone tetracarboxylic dianhydride was equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid. Polycondensation was carried out at 2.5°C for 6 h to obtain a carboxylated polyamic acid solution with a solid content of 20%.
[0081] The carboxylated polyamic acid solution was electrospun at a voltage of 15 kV, a receiving distance of 20 cm, and a feed speed of 1.25 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric was fixed on a stainless steel frame and subjected to pre-imidization heat treatment, which involved holding at 80℃ for 0.5 h, at 150℃ for 1 h, and then at 275℃ for 1 h. The carboxylated polyamic acid was thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0082] Hydroxyl-terminated hyperbranched polyester was dissolved in N-methylpyrrolidone to prepare a 20% (w / w) hydroxyl-terminated hyperbranched polyester solution. This solution was then mixed with the carboxylated polyamic acid solution at a dry weight ratio of 0.08:1. The mixture was stirred for 3 h and allowed to stand for 4 h to remove bubbles, resulting in a co-casting solution. The co-casting solution was then coated onto a polyimide nonwoven fabric to form a 300 μm thick wet film. The polyimide nonwoven fabric coated with the co-casting solution was immersed in water at 17.5°C for 5 s to pre-gel, and then transferred to a coagulation bath containing water and N-methylpyrrolidone at a weight ratio of 7:4 for 5.5 min to solidify into a film. After removal, the film was immersed in pure water for 2 h to wash, resulting in a solidified film.
[0083] The coagulated membrane was drained and subjected to thermosetting treatment. It was kept at 80℃ for 1 h, 150℃ for 1 h, and then at 250℃ for 1.5 h. The carboxylated polyamic acid was thermoiminated to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester were esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a thermosetting membrane. The thermosetting membrane was immersed in a 2% (w / w) zinc acetate aqueous solution for 2.5 h. The zinc ions were coordinated and crosslinked with the residual carboxyl groups in the separation layer. After removal, it was rinsed twice with ethanol and dried at 60℃ for 1.5 h to obtain a blended crosslinked nanofiltration membrane.
[0084] Example 4
[0085] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0086] Pentaerythritol and dimethylolpropionic acid were mixed at a molar ratio of 1:20, and p-toluenesulfonic acid was added at an amount of 0.75% of the total mass of pentaerythritol and dimethylolpropionic acid. Polycondensation was carried out at 145°C and a vacuum of 0.09 MPa for 4 h. After cooling to room temperature, the product was not purified to obtain a hydroxyl-terminated hyperbranched polyester.
[0087] Under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid were dissolved in N-methylpyrrolidone at a molar ratio of 7:3. After stirring and dissolving, benzophenone tetracarboxylic dianhydride was added in four portions. The molar amount of benzophenone tetracarboxylic dianhydride was equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid. Polycondensation was carried out at 2°C for 8 h to obtain a carboxylated polyamic acid solution with a solid content of 18%.
[0088] The carboxylated polyamic acid solution was electrospun at a voltage of 20 kV, a receiving distance of 18 cm, and a feed speed of 1 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric was fixed on a stainless steel frame and subjected to pre-imidization heat treatment, which involved holding it at 80℃ for 0.75 h, at 150℃ for 0.75 h, and then at 280℃ for 1.5 h. The carboxylated polyamic acid was thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
[0089] Hydroxyl-terminated hyperbranched polyester was dissolved in N-methylpyrrolidone to prepare a 15% (w / w) hydroxyl-terminated hyperbranched polyester solution. This solution was then mixed with the carboxylated polyamic acid solution at a dry weight ratio of 0.12:1. The mixture was stirred for 3 h and allowed to stand for 6 h to remove bubbles, resulting in a co-casting solution. The co-casting solution was then coated onto a polyimide nonwoven fabric to form a 250 μm thick wet film. The polyimide nonwoven fabric coated with the co-casting solution was immersed in water at 18°C for 15 s to pre-gel, and then transferred to a coagulation bath containing water and N-methylpyrrolidone at a weight ratio of 7:3 for 5 min to solidify into a film. After removal, the film was immersed in pure water for 3 h to wash, resulting in a solidified film.
[0090] The coagulated membrane was drained and subjected to thermosetting treatment. It was kept at 80℃ for 1 h, 150℃ for 1 h, and then at 240℃ for 1.5 h. The carboxylated polyamic acid was thermoiminated to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester were esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a thermosetting membrane. The thermosetting membrane was immersed in a 1% (w / w) zinc acetate aqueous solution for 2 h. The zinc ions were coordinated and crosslinked with the residual carboxyl groups in the separation layer. After removal, it was rinsed with ethanol 3 times and dried at 50℃ for 1.5 h to obtain a blended crosslinked nanofiltration membrane.
[0091] Comparative Example 1
[0092] The only difference from Example 4 is that the hydroxyl-terminated hyperbranched polyester is not incorporated into the separation layer. That is, the hydroxyl-terminated hyperbranched polyester solution is not prepared in step (1). Instead, the carboxylated polyamic acid solution is allowed to stand for 6 hours to degas and then scraped onto the polyimide nonwoven fabric. The remaining steps and parameters are the same as in Example 4, and a comparative film is obtained.
[0093] Comparative Example 2
[0094] The only difference from Example 4 is that the zinc acetate aqueous solution coordination crosslinking treatment is not performed. Instead, the thermosetting film is immersed in pure water for 2 hours, then rinsed with ethanol 3 times and dried at 50°C for 1.5 hours. The remaining steps and parameters are the same as in Example 4, resulting in a comparative film.
[0095] Comparative Example 3
[0096] The only difference from Example 4 is that the support layer uses commercially available polyethylene terephthalate nonwoven fabric, and the polyimide nonwoven fabric is not prepared by electrospinning with carboxylated polyamic acid solution. The remaining steps and parameters are the same as in Example 4, and a comparative film is obtained.
[0097] Comparative Example 4
[0098] The only difference from Example 4 is the method of film coagulation. The polyimide nonwoven fabric coated with the blend casting solution is directly immersed in pure water at 18°C for 5 minutes to coagulate into a film without water pre-gelling and mixing coagulation bath immersion. After removal, it is immersed in pure water for washing for 3 hours. The remaining steps and parameters are the same as in Example 4 to obtain the comparative film.
[0099] Comparative Example 5
[0100] The only difference from Example 4 is that the thermal imidization and esterification are carried out in two programmed heat treatments. That is, after the solidified film is drained, the first heat treatment is carried out by heating at 80°C for 1 h, 150°C for 1 h, and 240°C for 1.5 h to thermally imidize the carboxylated polyamic acid to form polyimide. After cooling to room temperature, the second heat treatment is carried out by heating at the same temperature to esterify the terminal hydroxyl groups of the hyperbranched polyester with the carboxyl groups in the carboxylated polyamic acid to form ester bonds. The remaining steps and parameters are the same as in Example 4, and a comparative film is obtained.
[0101] Performance Test Results and Analysis
[0102] The co-crosslinked nanofiltration membranes prepared in Examples 1-4 and the control membranes prepared in Comparative Examples 1-5 were cut into circular membrane pieces with an effective diameter of 47 mm and loaded into a cross-flow nanofiltration evaluation device. Astaxanthin ester and oleic acid were weighed and dissolved in anhydrous ethanol to prepare a solution with a mass concentration of 0.5 g / L for astaxanthin ester and 1.0 g / L for oleic acid, which was used as a simulated astaxanthin ester extraction solution. Nanofiltration separation performance tests were conducted at room temperature and an operating pressure of 0.8 MPa. The membrane was first pre-compressed with anhydrous ethanol for 30 min, and then a simulated astaxanthin ester extract was circulated. After stabilization, the feed solution, permeate, and concentrate were collected separately. The astaxanthin ester concentration was determined by measuring the absorbance at 478 nm using a UV-Vis spectrophotometer and then converted. The oleic acid concentration was determined by titrating the acid value with a potassium hydroxide ethanol standard solution and then converted. The astaxanthin ester rejection rate was calculated by subtracting the ratio of the permeate concentration to the feed solution concentration from 1 and then multiplying by 100%. The free fatty acid removal rate was calculated by the decrease rate of the concentrate acid value relative to the feed solution acid value. The flux was calculated by the volume of solution permeated per unit time, unit membrane area, and unit pressure. Molecular weight cutoff (MJ) tests were conducted using polyethylene glycol (PEG) solutions of 200 Da, 300 Da, 400 Da, 600 Da, 800 Da, and 1000 Da as solutes in ethanol solutions. The MJ cutoff for each fraction was determined using the same method. PEG concentration was measured using a total organic carbon analyzer. The PEG molecular weight at which a 90% MJ cutoff was achieved was taken as the membrane's MJ cutoff. Long-term operational stability tests were performed under the same equipment and conditions. A simulated astaxanthin ester extract was continuously run for 72 hours. Samples were taken every 24 hours to measure the astaxanthin ester cutoff and flux. The retention rate of the astaxanthin ester cutoff and the flux change rate after 72 hours of operation were calculated. Mechanical property tests involved cutting the membrane into dumbbell-shaped samples and using a universal testing machine at a tensile rate of 50 mm / min to determine tensile strength and elongation at break. For the interfacial bonding performance test, one end of the membrane was peeled off along the interface between the separation layer and the support layer, clamped on a universal testing machine, and subjected to a 180° peel at a tensile rate of 50 mm / min. The peel strength was recorded. The test results are shown in Table 1.
[0103] As shown in Table 1, the astaxanthin ester rejection rate of Examples 1-4 was 95.4%-97.5%, the free fatty acid removal rate was 93.5%-95.2%, and the flux was 52-62 L / (m²). 2 The molecular weight cutoff (molecular weight) was within the range of 500-700 Da, and the various indicators were well-matched, indicating that the network structure formed by the blended esterification crosslinking and zinc ion coordination crosslinking was complete. The separation layer did not swell in the ethanol feed solution, astaxanthin esters were stably retained, and free fatty acids passed through smoothly. Deacidification and concentration were completed in a single filtration. The aliphatic segments of the hydroxyl-terminated hyperbranched polyester were embedded in the rigid polyimide network, which adjusted the free volume of the separation layer, allowing the separation layer to maintain high throughput while maintaining retention accuracy.
[0104] Comparative Example 1, without the addition of hydroxyl-terminated hyperbranched polyester, relies solely on zinc ion coordination crosslinking in the separation layer, resulting in limited crosslinking strength. After swelling, the molecular weight cutoff of the separation layer increases to 750 Da, while the astaxanthin ester retention rate decreases to 90.1%. Furthermore, the lack of hydroxyl-terminated hyperbranched polyester to regulate free volume leads to dense packing of carboxylated polyamic acid, reducing the flux to 35 L / (m²). 2 The tensile strength (·h·MPa) was the lowest among all samples. During long-term operation, the coordination structure gradually dissociated under the flushing effect of the feed liquid, with a retention rate of only 82.5% and a throughput increase of 18.6%. The lack of ester-bonded covalent backbone also caused a simultaneous decrease in tensile strength and elongation at break. At the interface, the lack of esterification reaction also reduced the number of chemical bonding points, resulting in a decrease in peel strength. These data indicate that the blending of hydroxyl-terminated hyperbranched polyesters not only participates in the construction of the covalent crosslinking network but also plays a role in regulating the free volume of the separation layer, which is an indispensable feature of the technical solution of this application.
[0105] Table 1 Performance Test Results
[0106] Astaxanthin ester rejection rate, % 96.2 95.4 95.8 97.5 90.1 92.3 94.8 88.6 94.2 Free fatty acid removal rate, % 93.5 94.1 93.8 95.2 85.2 90.5 92.0 92.8 91.6 Flux, L / (m²·h·MPa) 58 52 55 62 35 50 49 45 51 Molecular weight cutoff, Da 580 640 600 550 750 800 630 950 710 72-hour retention rate, % 98.0 97.2 97.6 99.1 82.5 79.8 71.2 68.5 90.5 Flux change rate, % +3.2 +4.5 +3.8 +2.1 +18.6 +24.3 +35.2 +42.0 +9.8 Tensile strength, MPa 28.5 26.4 27.2 31.8 21.5 23.6 20.8 17.5 24.9 Elongation at break, % 15.2 13.8 14.5 17.6 10.5 8.4 12.2 9.8 13.0 Peel strength, N / 25mm 18.5 17.2 18.0 21.5 14.2 13.6 4.8 11.5 15.1
[0107] Comparative Example 2, without zinc acetate aqueous solution coordination crosslinking treatment, had only ester bonds as the chemical linking in the separation layer, with residual carboxyl groups not utilized. The crosslinking network was incomplete, the molecular weight cutoff increased to 800 Da, and the swelling of the separation layer also increased the effective separation layer thickness, reducing the flux to 50 L / (m²). 2 (·h·MPa). Its elongation at break was 8.4%, the lowest among all samples, which directly reflects the brittleness caused by single covalent crosslinking. Compared with the example, it can be clearly seen that the coordination bonds, due to their reversible dynamic characteristics, partially dissociate and reform under stress or solvent action, dissipating stress and alleviating the brittleness of the covalent crosslinking network. This is the basis for the beneficial effect of the separation layer taking into account mechanical properties. During long-term operation, its crosslinking network lacks dynamic adjustment space, swelling gradually accumulates, and the retention rate drops to 79.8%.
[0108] Comparative Example 3 used commercially available polyethylene terephthalate (PET) nonwoven fabric as the support layer. Its separation layer composition and preparation process were the same as in Example 4. Therefore, the initial rejection rate, removal rate, and retained molecular weight were similar to those of the examples. The main differences lay in the interfacial bonding and long-term operation. Its peel strength was only 4.8 N / 25 mm, far lower than the 17.2-21.5 N / 25 mm of the examples. This is because the support layer and separation layer of the examples were prepared from the same carboxylated polyamic acid solution, sharing the same material origin. During thermosetting and coordination treatment, esterification and coordination reactions also occurred at the interface, resulting in a chemical bond between the separation layer and the support layer. In contrast, the separation layer of Comparative Example 3 could only form a physical anchoring with the nonwoven fabric. After 72 hours of continuous operation, the interface of Comparative Example 3 gradually peeled off, and the liquid leaked through the peeling gap. The rejection rate retention rate decreased to 71.2%, while the throughput increased by 35.2%, corresponding to the interfacial peeling risk mentioned in the background art. This also confirms the practical value of the homologous polyimide nonwoven fabric support layer feature.
[0109] Comparative Example 4 eliminated the pre-gelling in water and the immersion in the mixed coagulation bath, directly immersing the film in pure water for coagulation. The rapid exchange between solvent and non-solvent resulted in instantaneous phase separation. Following the general principles of phase inversion membrane fabrication, under these conditions, perforated finger-like macropores easily formed on the cross-section, and defects in the skin layer were also prone to occur. The test data confirmed this, with the astaxanthin ester rejection rate dropping to 88.6%, the lowest among all samples, and the molecular weight cutoff reaching 950 Da. The separation layer could no longer accurately distinguish between free fatty acids and astaxanthin esters, and the removal rate and rejection rate decreased simultaneously, reflecting an overall failure of separation selectivity. During operation, the finger-like macropores expanded under pressure, and skin layer defects enlarged accordingly. The rejection rate retention rate further decreased to 68.5%, while the flux increased by 42.0%. The tensile strength also decreased to 17.5 MPa due to the reduced load-bearing capacity of the macropore structure. This data demonstrates that a two-stage coagulation method, involving pre-gelling in water followed by immersion in the mixed coagulation bath, is necessary to ensure skin layer integrity and uniform cross-sectional structure.
[0110] Comparative Example 5 performed thermal imidization and esterification in two separate programmed temperature heat treatments. After thermal imidization, the polyimide molecular chain was already fixed, and its mobility decreased. The contact between the terminal hydroxyl groups and carboxyl groups of the hyperbranched polyester was no longer sufficient, and the uniformity of esterification crosslinking deteriorated. Its molecular weight cutoff was 710 Da, exceeding the upper limit of the range. The astaxanthin ester retention rate, retention rate retention rate, flux change rate, and peel strength were all worse than those of the other examples, but better than those of Comparative Example 1 and Comparative Example 2, which lacked the entire crosslinking feature. This indicates that thermal imidization and esterification were completed in the same programmed temperature heat treatment, so that the skeleton shaping and crosslinking reaction were carried out simultaneously, and the crosslinking points were established before the molecular chain was completely fixed, which had a direct impact on the uniformity of the crosslinking network.
[0111] Test results show that the performance of each embodiment of this application is superior to that of the comparative examples. The comparative examples showed a significant decrease in at least one performance due to the absence or alteration of a single technical feature. This indicates that the combination of blended esterification crosslinking and zinc ion coordination crosslinking, the completion of thermal imidization and esterification in the same programmed temperature rise heat treatment, the homologous polyimide nonwoven fabric support layer, and the two-stage coagulation method together ensure the separation accuracy, operational stability, and reliability of the blended crosslinked nanofiltration membrane in the deacidification and concentration of astaxanthin ester extract.
[0112] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A blended crosslinked nanofiltration membrane, characterized in that, The nanofiltration membrane includes a support layer and a separation layer composited on the support layer; The support layer is a polyimide nonwoven fabric; the separation layer is obtained by blending carboxylated polyamic acid and hydroxyl-terminated hyperbranched polyester, solidifying the mixture into a film, and then subjecting it to thermal imidization, esterification, and coordination crosslinking. The thermal imidization and esterification are carried out in the same programmed temperature rise heat treatment; the esterification is the formation of ester bonds between the terminal hydroxyl groups of the terminal hydroxyl hyperbranched polyester and the carboxyl groups in the carboxylated polyamic acid; the coordination crosslinking is the coordination of zinc ions with the residual carboxyl groups in the separation layer. The carboxylated polyamic acid is obtained by copolymerization of benzophenone tetracarboxylic dianhydride, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the terminal hydroxyl hyperbranched polyester is obtained by polycondensation of pentaerythritol and dimethylolpropionic acid catalyzed by p-toluenesulfonic acid; the molecular weight cutoff of the separation layer is 500-700 Da.
2. The blended crosslinked nanofiltration membrane according to claim 1, characterized in that, The preparation method of the terminal hydroxyl hyperbranched polyester is as follows: pentaerythritol and dimethylolpropionic acid are mixed, p-toluenesulfonic acid is added, and polycondensation is carried out at 140-150℃ and vacuum degree 0.08-0.095 MPa for 3-6 h. After cooling to room temperature, the product is not purified to obtain the terminal hydroxyl hyperbranched polyester.
3. The blended crosslinked nanofiltration membrane according to claim 2, characterized in that, The molar ratio of pentaerythritol to dimethylolpropionic acid is 1:(12-28), and the amount of p-toluenesulfonic acid used is 0.5-1% of the total mass of pentaerythritol and dimethylolpropionic acid.
4. The blended crosslinked nanofiltration membrane according to claim 1, characterized in that, The method for preparing the carboxylated polyamic acid is as follows: under nitrogen protection, 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid are dissolved in N-methylpyrrolidone, stirred and dissolved, and then benzophenone tetracarboxylic dianhydride is added in 3-5 portions. The mixture is polycondensed at 0-5°C for 6-10 h to obtain a carboxylated polyamic acid solution with a solid content of 16-20%.
5. The blended crosslinked nanofiltration membrane according to claim 4, characterized in that, The molar amount of the benzophenone tetracarboxylic dianhydride is equal to the sum of the molar amounts of 4,4'-diaminodiphenyl ether and 3,5-diaminobenzoic acid; the molar ratio of 4,4'-diaminodiphenyl ether to 3,5-diaminobenzoic acid is 7:(2-4).
6. The blended crosslinked nanofiltration membrane according to claim 4, characterized in that, The carboxylated polyamic acid solution is electrospun at a voltage of 15-25 kV, a receiving distance of 15-20 cm, and a feed speed of 0.5-2 mL / h to obtain a carboxylated polyamic acid nonwoven fabric. The carboxylated polyamic acid nonwoven fabric is fixed on a stainless steel frame and subjected to pre-imidization heat treatment. The carboxylated polyamic acid is thermally imidized to form polyimide, resulting in a polyimide nonwoven fabric.
7. The blended crosslinked nanofiltration membrane according to claim 6, characterized in that, The steps and parameters of the pre-iminoization heat treatment are as follows: the carboxylated polyamic acid nonwoven fabric is kept at 80℃ for 0.5-1 h, at 150℃ for 0.5-1 h, and then at 250-300℃ for 1-2 h.
8. A method for preparing a blended crosslinked nanofiltration membrane as described in any one of claims 1-7, characterized in that, The method includes the following steps: (1) Dissolve the hydroxyl-terminated hyperbranched polyester in N-methylpyrrolidone to prepare a hydroxyl-terminated hyperbranched polyester solution with a mass fraction of 10-20%, mix it with the carboxylated polyamic acid solution, stir for 2-4 h, and let it stand to degas for 4-8 h to obtain a blended casting solution; coat the blended casting solution onto the polyimide nonwoven fabric to form a blended casting solution wet film with a thickness of 200-300 μm; (2) The polyimide nonwoven fabric coated with the co-casting solution in step (1) is immersed in water at 15-20℃ for 5-30 s to pre-gel, and then transferred to a mixed coagulation bath with a mass ratio of water to N-methylpyrrolidone of 7:(2-4) for 3-8 min to solidify into a film. After taking it out, it is immersed in pure water for 2-4 h to wash and obtain a solidified film. (3) Drain the solidified film and perform heat curing treatment. The carboxylated polyamic acid is heat imidized to form polyimide. The terminal hydroxyl groups of the hyperbranched polyester are esterified with the carboxyl groups in the carboxylated polyamic acid to form ester bonds, thus obtaining a heat-cured film. (4) Immerse the thermosetting membrane in a 0.5-2% zinc acetate aqueous solution for 1-4 h. The zinc ions coordinate and crosslink with the residual carboxyl groups in the separation layer. After removal, rinse with ethanol 2-3 times and dry at 40-60℃ for 1-2 h to obtain a blended crosslinked nanofiltration membrane.
9. The method for preparing a blended crosslinked nanofiltration membrane according to claim 8, characterized in that, The hydroxyl-terminated hyperbranched polyester solution and the carboxylated polyamic acid solution are mixed at a dry weight ratio of (0.08-0.2):
1. The steps and parameters of the thermosetting treatment are as follows: keep at 80℃ for 1 hour, keep at 150℃ for 1 hour, and then keep at 220-250℃ for 1-2 hours.
10. An application of the blended crosslinked nanofiltration membrane as described in any one of claims 1-7, characterized in that, The blended cross-linked nanofiltration membrane is used for deacidification and concentration of astaxanthin ester extract.